Efek Stres terhadap Pengobatan Asthma - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Ika Sandra Dewi; Romaito Nasution; Milna Sari (Pusat Riset dan Inovasi Nasional, 2024)
Stress has long been identified as a factor associated with poor asthma treatment outcomes; however, the magnitude of its effects and the underlying mechanisms remain unclear. In this meta-analysis, we evaluated the impact of stress on asthma management across 32 studies (N=47,892) published between 2014 and 2023. The results demonstrate a significant negative correlation between stress and asthma control (r=-0.42, 95% CI: -0.48 to -0.36, p<0.001), a positive correlation with symptom severity (r=0.38, 95% CI: 0.33 to 0.43, p<0.001), and a negative correlation with medication adherence (r=-0.29, 95% CI: -0.34 to -0.24, p<0.001). Additionally, the effect of stress was found to be stronger in adults compared to children (Q=7.89, p=0.005) and among individuals with low socioeconomic status (β=-0.018, p=0.010). Mechanistic analyses revealed the role of HPA axis activation (10 studies), autonomic dysfunction (7 studies), and increased pro-inflammatory cytokines (6 studies). In contrast to the findings of Sandberg et al. (2018), which focused on children, this study identifies a more pronounced effect in adults. Furthermore, these results extend the work of Chen et al. (2020) by highlighting a bidirectional relationship between stress and asthma outcomes (χ²=12.34, p=0.015), indicating a complex feedback cycle. We assert that these findings strengthen and broaden the conclusions of Yamauchi et al. (2016) by providing more precise effect estimates and a deeper mechanistic analysis. Consequently, this study underscores the importance of integrating stress assessment and psychosocial interventions in asthma management, with significant implications for developing more holistic and personalized care approaches.